Financial Performance on Corporate Social Responsibility Disclosure: Firm Size as Moderating Variable - Muhammad Yusuf; Nurhilalia Nurhilalia; Sitti Mujahida Baharuddin; Lukman Setiawan; Abdul Haris (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study examines and investigates the effect of financial ratios on stock returns in food and beverage manufacturing companies listed on the Indonesia Stock Exchange. This research is quantitative. The population in this study are all retail trading sub-sector companies listed on the Indonesia Stock Exchange from 2019 to 2021, totaling 35 companies. The sample selection in this study used the purposive sampling method; that is, only 11 companies were selected as samples. The data source in this study uses secondary data in the form of annual financial statements for the 2019-2021 period. The analytical method consists of panel data regression analysis with the help of eviews 12. The results show that financial performance as proxied by ROA has a positive and significant effect on retail trade CSR disclosures on the Indonesia Stock Exchange. Meanwhile, company size can moderate the impact of financial performance as proxied by ROA on retail trade CSR disclosures on the Indonesia Stock Exchange.